FACTORS AFFECTING THE KNOWLEDGE ABOUT STROKE RISKS AND EARLY SYMPTOMS IN EMERGENCY DEPARTMENT EAST JAVA - INDONESIA - Rachmawati, Dewi; Ningsih, Dewi Kartikawati; Andarini, Sri (Malang Neurology Journal, 2020)
BackgroundThe knowledge about stroke risks and early symptoms is pivotal to minimize the arrival delay in the hospital and maximize the effective treatments.ObjectiveInvestigating the factors affecting the knowledge about stroke risks and early symptoms in the emergency department (ED).MethodsThe study employed a cross-sectional design by means of a prospective approach. Samples were taken by consecutive sampling technique recruiting in a total of 58 respondents. The respondents were the family or relatives of acute ischemic stroke patients who happened to know and directly involved in taking the patients to the ED. Data analyzed by utilizing univariate analysis, independent t-test, and one-way ANOVA to determine the differences in the knowledge of every respondent based on several characteristics. Multivariate analysis was used to investigate the factors affecting the knowledge about stroke risks and early symptoms.ResultsThe average age of the 58 respondents was 34 – 57 years old. 46.5% of whom were graduating from primary school; 51.7% have never been equipped with the necessary information about stroke; 55.2% are female, and 50% of whom were unemployed. There were differences in the knowledge about stroke risks based on the prior information about stroke and education background. As for stroke early symptoms, there were differences towards occupations, prior information about stroke, and education background. The most affecting factor towards the knowledge of stroke risks is education background (p=0.000); while the knowledge about stroke early symptoms were mostly affected by prior information about stroke (p=0.012) and education background (p=0.000).Discussions Most respondents were less equipped with the necessary knowledge about stroke risks and symptoms. The respondents’ knowledge about stroke risks and early symptoms was considered less, while education background was the affecting factor towards the knowledge about stroke risks and symptoms.